2017
DOI: 10.1001/jamafacial.2016.1544
|View full text |Cite
|
Sign up to set email alerts
|

Human Induced Pluripotent Stem Cell–Derived Motor Neuron Transplant for Neuromuscular Atrophy in a Mouse Model of Sciatic Nerve Injury

Abstract: IMPORTANCE Human motor neurons may be reliably derived from induced pluripotent stem cells (iPSCs). In vivo transplant studies of human iPSCs and their cellular derivatives are essential to gauging their clinical utility.OBJECTIVE To determine whether human iPSC-derived motor neurons can engraft in an immunodeficient mouse model of sciatic nerve injury. DESIGN, SETTING, AND SUBJECTSThis nonblinded interventional study with negative controls was performed at a biomedical research institute using an immunodefici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 27 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…In particular, the realization that Oct4, Sox2, Klf4 and Myc can reprogram easily obtained cell types to pluripotency has fueled new approaches to studying human disease. By reprogramming cells from individuals with genetic forms of disease into induced pluripotent stem cells (iPSCs) or somatic cell types, it has become possible to understand and develop interventions for cell type-specific pathologies that previously could have only been studied using postmortem tissues (Blanchard et al, 2015;Brennand et al, 2011;Ichida et al, 2009Ichida et al, , 2014Ichida and Kiskinis, 2015;Kiskinis et al, 2014;Kramer et al, 2018;Mertens et al, 2015;Pepper et al, 2017;Shi et al, 2018;Son et al, 2011;Takahashi et al, 2007a,b;Toma et al, 2015;Wainger et al, 2015;Wen et al, 2014;Wilkinson et al, 2018;Xu et al, 2015;Zhang et al, 2015;Zhao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the realization that Oct4, Sox2, Klf4 and Myc can reprogram easily obtained cell types to pluripotency has fueled new approaches to studying human disease. By reprogramming cells from individuals with genetic forms of disease into induced pluripotent stem cells (iPSCs) or somatic cell types, it has become possible to understand and develop interventions for cell type-specific pathologies that previously could have only been studied using postmortem tissues (Blanchard et al, 2015;Brennand et al, 2011;Ichida et al, 2009Ichida et al, , 2014Ichida and Kiskinis, 2015;Kiskinis et al, 2014;Kramer et al, 2018;Mertens et al, 2015;Pepper et al, 2017;Shi et al, 2018;Son et al, 2011;Takahashi et al, 2007a,b;Toma et al, 2015;Wainger et al, 2015;Wen et al, 2014;Wilkinson et al, 2018;Xu et al, 2015;Zhang et al, 2015;Zhao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The control 03231 iPSC line was generated from a lymphoblastoid cell line derived from a healthy 56 year-old male (NINDS repository, ND03231) as previously described (34). For gene-editing, guide RNAs were cloned into pSpCas9(BB)-2A-Puro (PX459) V2.0 and the homologous recombination donor vector was constructed using the pFETCH_Donor plasmid (35,36).…”
Section: Cell Culture and Neural Differentiationmentioning
confidence: 99%
“…Both ESCs and iPSCs differentiated toward NS/PCs or glial cells have been transplanted directly into the spinal cord of rodent models of ALS. Human cells have been observed within transplanted animals up to 9 months post‐transplantation and have been shown to form neurites, axons, and even functional neuromuscular junctions . However, the terminal differentiation of these cells is variable.…”
Section: Human–animal Chimerismmentioning
confidence: 99%
“…Two separate groups observed that up to 1,600,000 human cells integrated into the spinal cord of mutant SOD1 transgenic rodents up to 9 months post‐transplant, with the majority of transplanted human cells differentiating toward astrocytes . Although some studies have shown grafted human neural stem cells to extend axons and innervate muscle, it is likely that the benefits seen are at least in part due to the neuroprotective mechanisms exerted by the engrafted human cells .…”
Section: Human–animal Chimerismmentioning
confidence: 99%